Kesalahan dalam Penggunaan Ragam Unggah-ungguh Basa Jawa pada Film Pendek Capciptop! 2020 - Miftahul Izza; Bagus Wahyu Setyawan (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2024)
The variety of language and language is the hallmark of the Javanese. This value has been embedded in society for a long time. This has become an unwritten rule. Most Javanese people will judge someone's politeness from the way they speak so that they can know whether the person has good behavior or not. Unfortunately, sometimes people neglect important things like this. This is caused by the development of the times. As times progress, people tend to follow Western culture. Meanwhile, Western culture does not have a speech classification between speakers and speech partners. Therefore, researchers are interested in studying errors in the use of uploading bases in the Capciptop! short film released in 2020 using a descriptive qualitative approach with data collection techniques, namely note-taking. The results of the study found that there were five errors in the short film. Three errors lie with the speaker while the other two lie with the speech partner. The form of the mistake is not using polite manners when speaking to older people.